2015
DOI: 10.1136/bjophthalmol-2014-306366
|View full text |Cite
|
Sign up to set email alerts
|

Increased vitreous concentrations of MCP-1 and IL-6 after vitrectomy in patients with proliferative diabetic retinopathy: possible association with postoperative macular oedema

Abstract: The elevated levels of MCP-1 and IL-6 may indicate prolonged inflammation even after successful vitrectomy, which can cause postoperative DME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 25 publications
(34 reference statements)
4
39
0
8
Order By: Relevance
“…Other studies have demonstrated that the activation of the IL-6 trans-signaling pathway induced the phosphorylation of STAT3 resulting in an increase in VEGF production [24,25]. From these findings, we suggest that the reduced level of intravitreal VEGF concentration after vitrectomy [18] gradually recovers by the stimulation of these upregulated inflammatory cytokines. This should then lead to the slower recovery of CMT and the prolongation of DME by the anti-VEGF drug in the vitrectomized eyes.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Other studies have demonstrated that the activation of the IL-6 trans-signaling pathway induced the phosphorylation of STAT3 resulting in an increase in VEGF production [24,25]. From these findings, we suggest that the reduced level of intravitreal VEGF concentration after vitrectomy [18] gradually recovers by the stimulation of these upregulated inflammatory cytokines. This should then lead to the slower recovery of CMT and the prolongation of DME by the anti-VEGF drug in the vitrectomized eyes.…”
Section: Discussionsupporting
confidence: 52%
“…We have shown that the intravitreal concentration of VEGF is lower [17] and the concentration of inflammatory cytokines such as IL-6 and MCP-1 is higher at approximately 7 months after successful vitrectomy [18]. We believe that these inflammatory cytokines might induce prolonged DME after vitrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these proteins have been documented in other studies to date, notably IL-6, IL-8, and MCP-1. [41][42][43][44][45] Cohen et al 42 demonstrated an association between the inflammatory factor IL-6 and VEGF, showing IL-6 may function upstream of VEGF. Interleukin-8 has also been identified as a key mediator in ocular inflammation and ischemic disease.…”
Section: Inflammation In Ischemic Retinal Diseasementioning
confidence: 99%
“…The concentration of ligands for C-C chemokine receptor types 2 (CCR2; primary ligand: monocyte chemoattractant protein-1 [MCP-1]) and 5 (CCR5; primary ligand: RANTES) are elevated in the vitreous and aqueous humors of patients with diabetic retinopathy/DME. 4,[26][27][28][29][30][31][32] CCR2 and CCR5, expressed on the surface of monocytes, 33,34 play a key role in inflammation and in the homing of inflammatory cells to their target tissues. Preclinical studies have linked the CCR2 pathway with vascular leakage from, and monocyte infiltration into, the retina in experimental diabetes.…”
mentioning
confidence: 99%